Influência do empacotamento da areia no desempenho dos compósitos cimentícios - Joaquim Francisco Tavares Junior (2018)
The granulometry of fine aggregates influences the cement composites´ performance and, depending on the used gradation of sand, may enable packaging. In literature, many studies investigate the packaging of fine aggregate by changing the water/cement ratio and/or by introducing additives or additions to improve workability. In a different setting, this work studies the influence of particle packing on the properties of cement composites made with natural fine aggregates of the same or different granulometries, keeping the water/cement ratio constant. Experimental results were obtained with mortars composed of same sand granulometry (0.3mm, 0.6mm and 1.2mm) and packing the three granulometries in the same proportion, each for both fresh and hardened states. The use of 0.3mm sand granulometry influences negatively the cement composites performance in both states. Composites with 0.6mm and 1.2mm sand granulometry show similar behavior among themselves. The packing composite results show increased workability, compressive strength, flexion traction, dynamic modulus of elasticity and electrical strength in relation to 0.3mm granulometry. Packaging also reduced water absorption and porosity compare it. Results show that packing composite maximizes concrete performance, except compressive strength at early ages.